OPTIMIZATION OF RICE PRODUCT SALES AT BONE INDAH TDM SHOPS USING LINEAR PROGRAM - Ninia Lina, Tirsa; Rumetna, Matheus Supriyanto; Karay, Jeni; Greogory Kaitelapatay, Big; Budi Santoso, Agustinus; Komansilan, Reinhard (Journal of Computer Science and Technology (JCS-TECH), 2023)
The Bone Indah TDM shop is a rice selling business located on Jalan Basuki Rahmat, Sorong City, Southwest Papua, Indonesia. Store managers need the right way to continue to make a profit and develop their rice sales business, because the competition is getting higher. The problem of optimizing rice sales that has been experienced by Bone Indah TDM Stores can be overcome by one of the methods contained in the linear program, namely simplex and combined with POM-QM software for Windows version 5. The data used to optimize rice sales is type data product, product size, product stock to profit. All of these data were obtained through observation and interviews. The results obtained are that the Bone Indah TDM Store gets a profit of IDR 2,898,551 per month.